2002
DOI: 10.1002/hon.698
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute lymphoblastic leukemia in Hong Kong children: HKALL 93 study

Abstract: A population-based multicentre study for childhood acute lymphoblastic leukemia (ALL) was conducted in Hong Kong from 1993 to 1997. One hundred and forty-five newly diagnosed ALL patients were treated by the HKALL 93 protocol. Patients were stratified into three risk groups according to age, presenting white cell count, immunophenotyping and cytogenetic study. The patients received the same induction and early and late intensification at week 5 and week 20. Fifty-eight standard risk (SR) patients received regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
4
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
2
13
4
3
Order By: Relevance
“…Japan [18] and Hong Kong [19] have reported incidences of 48 and 57% respectively, figures that are lower than those reported by UKALLXI2001 [20] and CCG [17] for other races. However, our results indicate that 121 (92%) patients out of a study group of 132 had chromosomal abnormalities, an incidence higher than previously reported regardless of race.…”
Section: Discussioncontrasting
confidence: 64%
“…Japan [18] and Hong Kong [19] have reported incidences of 48 and 57% respectively, figures that are lower than those reported by UKALLXI2001 [20] and CCG [17] for other races. However, our results indicate that 121 (92%) patients out of a study group of 132 had chromosomal abnormalities, an incidence higher than previously reported regardless of race.…”
Section: Discussioncontrasting
confidence: 64%
“…In contrast, some authors reported that the WBC count is a significant prognostic factor. [15][16][17][18] In conclusion, compared with reports from developed countries, our data with modified ALL-BFM 95 showed a lower EFS and a higher mortality rate in CR although a satisfying remission rate and DFS. The protocols and establishment of strategies to reduce deaths from infection in CR must be our priority.…”
Section: Discussioncontrasting
confidence: 50%
“…5 TRM commonly causes treatment failure in LICs. Whereas ALL in HICs has been associated with TRM rates of 1% to 3%, [6][7][8][9][10][11] the few studies that have investigated LICs have identified rates from 11% to 21%. 4,[12][13][14][15] In El Salvador, 12.5% of children with ALL experienced TRM.…”
mentioning
confidence: 99%